2013
DOI: 10.1016/j.dnarep.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of homologous recombination with vorinostat synergistically enhances ganciclovir cytotoxicity

Abstract: The nucleoside analog ganciclovir (GCV) elicits cytotoxicity in tumor cells via a novel mechanism in which drug incorporation into DNA produces minimal disruption of replication, but numerous DNA double strand breaks occur during the second S-phase after drug exposure. We propose that homologous recombination (HR), a major repair pathway for DNA double strand breaks, can prevent GCV-induced DNA damage, and that inhibition of HR will enhance cytotoxicity with GCV. Survival after GCV treatment in cells expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The comet assay and γ-H2AX foci experiments by Ladd et al have shown that HSV-TK/GCV can cause DNA double-stranded breaks [ 25 ], which are frequently irreversible and result in cell death [ 7 ]. Such DNA damage can increase levels of ATM (ataxia telangiectasia mutated) and ATR (ATM-Rad3-related), both of which induce phosphorylation of serine 15 on p53; this prevents the interaction of MDM2 with p53 and reduces p53 ubiquitination and degradation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The comet assay and γ-H2AX foci experiments by Ladd et al have shown that HSV-TK/GCV can cause DNA double-stranded breaks [ 25 ], which are frequently irreversible and result in cell death [ 7 ]. Such DNA damage can increase levels of ATM (ataxia telangiectasia mutated) and ATR (ATM-Rad3-related), both of which induce phosphorylation of serine 15 on p53; this prevents the interaction of MDM2 with p53 and reduces p53 ubiquitination and degradation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDACi’s have been shown to directly downregulate homologous recombination and non-homologous end-joining in many cancer cell lines [ 17 - 20 ]. For example, in prostate cells, treatment with HDACi downregulates the protein expression levels of BRCA1, RAD51 and DNA-PK, and the mRNA expression levels of ATM, BRCA1, BRCA2, RAD51 and XRCC4 [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect sensitizes cells to DNA double-strand breaks, a genotoxic event playing a critical role in cancer cell survival [ 61 ]. Other anticancer drugs, such as bortezomib, imatinib, and histone deacetylase inhibitors, target homologous recombination [ 62 64 ]. This evidence might encourage further studies to test the effect of pomegranate extract in association with the anticancer drugs above reported.…”
Section: Anticancer Activity Of Pomegranate Polyphenolsmentioning
confidence: 99%